Consequences of the Ex Parte Communications in the Arbi- tration between Croatia and Slovenia - Runjić, Ljubo (Pécs journal of international and European law, 2019)
Public disclosure of the ex parte communications in the arbitration between Croatia and Slovenia has given rise to a situation without precedent in the history of international arbitration. This ar- ticle analyzes from the international law point of view the consequences of the telephone conver- sations between Dr. Sekolec, the arbitrator appointed by Slovenia and Ms. Simona Drenik, Agent of Slovenia. There is no doubt that the fundamental principles of the arbitration process, including due process, procedural fairness, impartiality and independence have been violated in the arbi- tration between Croatia and Slovenia to the prejudice of Croatia. Considering the essential im- portance that those principles have in the international arbitral proceedings and rendering a fair and just award, as well as political connotations of the ex parte communication, this article argues that the proceedings should have been terminated. In addition, this article argues that Slovenia’s actions, i.e. the ex parte communication constitute a material breach of the Arbitration Agreement because they defeated one of the objects and purposes of the Arbitration Agreement – the settlement of the maritime and land boundary dispute between Croatia and Slovenia in accordance with the rules and principles of international law, equity and the principle of good neighbourly relations in order to achieve a fair and just result. Therefore, Croatia was entitled to terminate the Arbitration Agreement under Article 60, paragraph 1 of the Vienna Convention on the Law of Treaties.